Connectivity conservation - Crooks, Kevin R.; Sanjayan, M. A., 1966-; Cambridge eBooks (Cambridge : Cambridge University Press, 2006)
One of the biggest threats to the survival of many plant and animal species is the destruction or fragmentation of their natural habitats. The conservation of landscape connections, where animals, plants, and ecological processes can move freely from one habitat to another, is therefore an essential part of any new conservation or environmental protection plan. In practice, however, maintaining, creating, and protecting connectivity in our increasingly dissected world is a daunting challenge. This fascinating volume provides a synthesis on the current status and literature of connectivity conservation research and implementation. It shows the challenges involved in applying existing knowledge to real-world examples and highlights areas in need of further study. Containing contributions from leading scientists and practitioners, this topical and thought-provoking volume will be essential reading for graduate students, researchers, and practitioners working in conservation biology and natural resource management.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Biodiversity conservation; Biocomplexity; Electronic books